Educação popular, movimentos sociais e a atuação do Centro de Educação Popular nas ações de desenvolvimento territorial - Matos, Silvana Pires de (2021)
This research is presented to the Graduate Program in Geography at UNIOESTE- Francisco Beltrão, in the line of research on Economic Development and territorial dynamics. Having as its object of study the Centro de Educação Popular (Popular Education Center), or CEPO, of Erechim-RS, an institution founded in 1985 with the purpose of planning and uniting people with the Movement that was emerging in the region of the Alto Uruguai of Rio Grande do Sul (RS). We aim into investigate how CEPO contributed to territorial development of the Alto Uruguai -RS region through the Popular Education. In this regard, the territorial approach is central to discussing and expanding the debate on Social Movements and Popular Education. Aiming to respond to the proposed objective, we used 1985 to 2005 as a time frame for the research, making use of qualitative approach. As methodological tools we used: (1) Estado da Arte (State of the Art) on the Biblioteca Digital de Teses e Dissertações (Digital Library of Theses and Dissertations) website or BDTD; (2) afterward we used the Abordagem Textual Discursiva (Discursive Textual Approach) or ATD to analyze the analytical categories that emerged from the works found; (3) theoretical basis on Social Movements, Popular Education, territory and territoriality; (4) documentary research, that is, analysis of CEPO documents, at this stage of the research we seek to complement the bibliographic review and research at Estado da Arte, advancing the understanding of the entity's performance in the region and its contribution to regional territorial development; finally, (5) we concluded the research by conducting interviews with subjects who worked at CEPO, or who were somehow linked to projects and work developed by the institution. We were able to identify how CEPO contributed to the territorial development of the region, as it enabled the construction of new knowledge and understanding of the reality that farmers and other subjects in the region lived, confronting the local reality with the vision of capital, reflecting and building on the collective public policies based on their reality.